Desempenho, características de carcaça e qualidade de carne de novilhas mestiças gestantes ou não terminadas em confinamento - Macedo, Lívia Maria Araújo (2007)
This work was carried out to evaluate the effect of pregnancy on performance, carcass traits, chemical and fatty acids composition of five meat cuts (chuck, rump, striploin, topside and knucle) and compare the chemical and fatty acids composition among cuts from crossbreed heifers (½ Nellore vs ½ Charolais) finished in feedlot. Ten heifers were used: five pregnant (90 days of pregnancy) and five nonpregnant with 20 months of age and initial average weight of 327 kg. The heifers were kept in a star grass paddock and received diets composed by 50% of corn silage and 50% of concentrate (corn, soybean meal, soybean hulls, urea and mineral salt) that was fed twice a day (8:00 am and 4:00pm). The heifers were kept in feedlot during 67 days and were weighted each 21 days, before first feed. The mean slaughter weight was 407.20 kg. The performance and carcass traits were not influenced (P>0.05) by physiological condition of heifers. The physiological condition at slaughter did not alter meat nutritive value. The top side and knuckle had a lower risk to human health considering the fatty acids.